2012
DOI: 10.1007/s00296-012-2419-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis endocervical infection in systemic lupus erythematosus patients and evaluation of the risk for HPV-induced lesions

Abstract: Chlamydia trachomatis (CT) is the most common bacterial cause of sexually transmitted disease. It has been associated with arthritis and it is a risk factor for human papillomavirus (HPV)-induced lesions. There are few studies on the frequency of CT infection among systemic lupus erythematosus (SLE) patients. The aim of this study was to determine the prevalence of endocervical CT infection among SLE patients and evaluate whether or not CT infection is a risk factor for HPV-induced lesions. A cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Rojo-Contreras et al (5) recently found a prevalence of 14.7% in Mexican SLE patients. In contrast, a Brazilian study found a prevalence of 80.7% (9). These differences may be due to environmental, cultural, or genetic risk factors or geographical variations (23).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Rojo-Contreras et al (5) recently found a prevalence of 14.7% in Mexican SLE patients. In contrast, a Brazilian study found a prevalence of 80.7% (9). These differences may be due to environmental, cultural, or genetic risk factors or geographical variations (23).…”
Section: Discussionmentioning
confidence: 88%
“…However, some studies have found no association between cervical HPV infection and immunosuppressive therapy (3,9). In recent years, new, targeted therapies have been administered to SLE patients, and there has been some evidence for the efficacy and safety of B cell depletion by anti-CD20 therapy with rituximab.…”
Section: Introductionmentioning
confidence: 99%
“… 18 A study assessed C. trachomatis by vaginal swab test and did not find an increased prevalence in patients with SLE. 32 Another study investigated the potential relationship between coronary calcifications as a marker of atherosclerotic burden and PCR for C. pneumonia e and C. trachomatis in the peripheral blood monocytes of patients with SLE, without finding a clear association. 33 Most patients with SLE included in our study had disease features beyond articular and cutaneous involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the patients are shown in Table 1. There were eight studies 8,19,24,26,27,[29][30][31] focused on cervical cancer, seven studies 2,10,20,22,23,25,33 on squamous intraepithelial lesion (SIL) and six studies 10,20,22,23,25,33 approaching risk of lowgrade SIL (LGSIL).…”
Section: Study Characteristicsmentioning
confidence: 99%